PENGARUH MODEL PELATIHAN KADER DALAM MEMANFAATKAN ALAT ANTROPOMETRI UNTUK MENDETEKSI STUNTING DI PUSKESMAS DOREKAR - Anisa Qadarsi Ananda Hamsah; Purwadhi, Purwadhi; Nining Handayani (Bajang Institute, 2025)
The stunting prevalence rate indicates the percentage of toddlers whose height is below the standard for their age, indicating chronic nutritional problems. Stunting is a complex health problem, which not only impacts children's physical growth, but also cognitive development and long-term productivity. Therefore, handling stunting requires a holistic approach and strong collaboration between the government, the community, and various related sectors. This study aims to determine the effect of simulation training models and conventional training models (lectures) in detecting stunting and to determine the most dominant effect between simulation training and conventional training (lectures) in detecting stunting at the Dorekar Community Health Center. This study used a quantitative approach with a quasi-experimental pre-test and post-test with a control group design. The results of this study indicate that there is an effect between the simulation training model and conventional training (lectures) on improving the ability of cadres in detecting stunting at the Dorekar Community Health Center (p = .001). The analysis of the difference test showed that the simulation model has a more significant effect than conventional training (lectures) on improving the ability of cadres in detecting stunting (p = .001). The conclusion is that there is an increase in the cadre's abilities after participating in training using simulation methods and conventional methods (lectures), and the simulation training model is more influential than the conventional training model (lectures) in improving the cadre's abilities.